2016
DOI: 10.1080/14732971.2016.1248129
|View full text |Cite
|
Sign up to set email alerts
|

The lost lochs of Scotland: tracking land-use change and its effects on the archaeological record

Abstract: This paper examines how loch drainage in 18 th and 19 th century Scotland has shaped the archaeological record, with particular reference to lake dwellings known as 'crannogs'. The analysis uses the Roy Military Survey of Scotland (1747-55) as a base-line for charting changes to lacustrine environment through time. The work is unique for its scale which examines all of mainland Scotland, and the results have revealed unrecognised patterns in the timing and intensity of land-use changes that have impacted lacus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Recent work testing the distribution of crannogs across the country has shown that crannogs were more widespread in north-east Scotland than previously considered, with 33 possible sites now identified in the modern council areas of Aberdeenshire, Aberdeen City, Angus, Moray and Fife (a near three-fold increase on previous counts), though most have been impacted by drainage (Stratigos 2016a(Stratigos , 2016b(Stratigos , 2017) (Illus 1). The new investigation of crannogs in north-east Scotland reported on here responded to calls for greater sampling of sites to build chronologies with the aim of constructing frameworks that assessed the adoption and use of crannogs across Scotland (Dixon 2004: 176-7;Dixon et al 2007: 683;Crone 2012: 164-5), but with this greater presence of crannogs in the study area in mind.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent work testing the distribution of crannogs across the country has shown that crannogs were more widespread in north-east Scotland than previously considered, with 33 possible sites now identified in the modern council areas of Aberdeenshire, Aberdeen City, Angus, Moray and Fife (a near three-fold increase on previous counts), though most have been impacted by drainage (Stratigos 2016a(Stratigos , 2016b(Stratigos , 2017) (Illus 1). The new investigation of crannogs in north-east Scotland reported on here responded to calls for greater sampling of sites to build chronologies with the aim of constructing frameworks that assessed the adoption and use of crannogs across Scotland (Dixon 2004: 176-7;Dixon et al 2007: 683;Crone 2012: 164-5), but with this greater presence of crannogs in the study area in mind.…”
Section: Introductionmentioning
confidence: 98%
“…The presence of artificial island dwellings, or 'crannogs', in Scotland has been recognised since the 18th century, and were the target of antiquarian investigation from the mid-19th century (Stuart 1866;Munro 1882;Blundell 1909). North-east Scotland saw early work on crannogs (Burnett 1851;Grigor 1863;Stuart 1874), but since then there has been relatively little interest in crannogs of this region until recently (Stratigos & Noble 2014;Stratigos 2016aStratigos , 2016bStratigos , 2017. Modern investigations of crannogs in Scotland have tended to focus on regions where there was a more robust and established track record of antiquarian researchlike south-west Scotland (Barber & Crone 1993;Henderson et al 2006;Cavers et al 2011) -or where there were more numerous extant submerged siteslike Loch Awe (McArdle et al 1973) and Loch Tay (Dixon 1981).…”
Section: Introductionmentioning
confidence: 99%